Embracing ‘Abolition Ecology’: a green criminological rejoinder - Griffin, Nathan Stephens (Critical criminology, 2023)
Recent debates in political ecology have sought to highlight and excavate the complex connectivity between ecological and carceral harms (e.g. Heynen and Ybarra in Antipode 53:21-35, 2021; Pellow 2021; Pulido and De Lara in Environ Plan E Nat Space 1:76-98, 2018; AAA = Brock and Stephens-Griffin, IDS Bulletin, 2017). ‘Abolition ecology’ presents an approach through which to explore, unravel and resist racial capitalism and environmental racism as interlocking and mutually generative systems (Heynen in Abolit A J Insurg Polit 1:240-247, 2018a; Pulido in Prog Hum Geogr 41:524-533, 2017). Green criminology is a field well-placed to explore such radical possibilities (Bradshaw in Crit Criminol 26:407-422, 2018). This paper offers a green criminological rejoinder to the bourgeoning project of ‘abolition ecology’. The paper works to bring together these linked perspectives, asking how green criminology might contribute to abolition ecology. The paper outlines its abolitionist theoretical framework, and then identifies some benefits of a green criminological orientation. It goes on to suggest three possible points of unity between green criminology and abolition ecology. In embracing these points of unity, and abolitionist principles more broadly, green criminology can better work towards more racially and ecologically just futures.